Phytol-containing seaweed extracts as control for Ganoderma boninense - Abdul Aziz, Syamimi Diyana; Jafarah, Nur Fazirah; Balia Yusof, Zetty Norhana (Malaysian Palm Oil Board, 2019)
Basal stem rot (BSR) is a disease in oil palm caused by a fungal pathogen, Ganoderma boninense. Utilisation of seaweeds as a control agent has not been explored. This study investigated the anti-fungal potential of Malaysian seaweed extracts against G. boninense and identification of the compounds. Seaweeds cfSargassum oligocystum, Caulerpa racemosa, Caulerpa racemosa var. lamouroxii and cfHalimeda macrophysa were collected and subjected to crude extraction with various solvents. Methanolic extracts of all species displayed the highest yield with an average of 15.25% compared to dry weight. Anti-fungal assays were carried out against G. boninense using the poisoned food technique and three highest inhibitions were exhibited by C. racemosa var. lamouroxii dichloromethane extract (46.82%), cf H. macrophysa dichloromethane extract (33.49%) and C. racemosa methanol extract (28.06%). Dominant compounds detected via gas chromatography-mass chromatography (GC-MS) in extracts with anti-fungal potential includes phytol. Anti-fungal assay using standard phytol showed growth inhibition of G. boninense of up to 21% inhibition. Caulerpa racemosa var. lamouroxii, cf H. macrophysa, C. racemosa and cf S. oligocystum dichloromethane extracts contain 474, 117, 106 and 19 mg litre-1 of phytol respectively. These findings suggested that Malaysian seaweeds are a good source of anti-fungal compounds for utilisation in controlling the BSR disease of oil palm in Malaysia.